Management physiotherapy for cervical root syndrome with ultrasound, nerve mobilization and exercise: a case report - Salsabila, Dika Tiara; Pristanto, Arif; Fauzan, Muhammad (Journal of Health Management and Pharmacy Exploration, 2025)
Cervical Root Syndrome (CRS) is an abnormal condition caused by irritation or compensation of the cervical nerve roots, which can occur due to trauma. Arthritis, or compression of the intervertebral discs in the neck area. This research is to determine the benefits of providing ultrasound (US) modalities, nerve mobilization, isometric exercises, and stretching in CRS cases. The measurements used are pain measurement using the Numerical Rating Scale (NRS), Range of Motion (ROM) measurement using a goniometer, muscle strength measurement using Manual Muscle Testing (MMT), and functional activity measurement using the Neck Disability Index (NDI). The research was carried out directly on a patient with CRS condition by administering therapy in three meetings with physiotherapy intervention.  After 3 therapy meetings carried out by the physiotherapy program for Cervical Root Syndrome with physiotherapy modalities in the form of US, nerve mobilization, isometric exercises and stretching, significant changes were seen in reducing pain, increasing joint range of motion, muscle strength and functional ability.